2022
DOI: 10.4103/jpbs.jpbs_187_22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Role of Complete Dentures in Improving the Chewing Efficiency of Edentulous Patients

Abstract: Introduction: The loss of teeth leads to difficulty in chewing and smiling and an unesthetic appearance. The present study assessed the role of complete dentures in improving the chewing efficiency of edentulous patients. Materials and Methods: Eighty-two complete denture wearers of age group 40–75 years of both genders were enrolled in the study. The chewing efficiency of denture was determined by VMM machine. Patients were provided with the self- administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The masticatory function of the complete-denture wearers is relatively poor compared to that of healthy dentate subjects. Complete-denture wearers need up to seven times more chewing strokes than subjects with a complete natural dentition to reduce the food to half the original particle size ( Emami et al, 2013 ; Kumari et al, 2022 ). Other studies have reported that patients rehabilitated with CDs demonstrated significantly lower masticatory functions ( Slagter et al, 1992 ; Wayler & Chauncey, 1983 )…”
Section: Introductionmentioning
confidence: 99%
“…The masticatory function of the complete-denture wearers is relatively poor compared to that of healthy dentate subjects. Complete-denture wearers need up to seven times more chewing strokes than subjects with a complete natural dentition to reduce the food to half the original particle size ( Emami et al, 2013 ; Kumari et al, 2022 ). Other studies have reported that patients rehabilitated with CDs demonstrated significantly lower masticatory functions ( Slagter et al, 1992 ; Wayler & Chauncey, 1983 )…”
Section: Introductionmentioning
confidence: 99%
“…One general method for overcoming decreased chewing ability is the use of partial or full dentures, and the number of people using dentures is increasing [ 13 ]. However, chewing ability does not improve immediately with denture wear because of difficulties in maintaining and adopting dentures due to issues such as a loss of oral mucous membrane elasticity, alveolar bone resorption, and xerostomia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%